Enteral feeding is associated with longer survival in the advanced stages of prion disease. Issue 1 (10th September 2019) - McNiven, Kirsty; Nihat, Akin; Mok, Tze How; Tesfamichael, Selam; O'Donnell, Veronica; Rudge, Peter; Collinge, John; Mead, Simon
Abstract: To report the frequency, complications, survival and motivations for enteral feeding in UK patients with prion diseases. We analysed data from an ongoing prospective observational cohort study of UK patients with prion diseases ( n = 635). Gastrostomy-treated cases were matched by age, gender, disease aetiology, severity, duration and a genetic predictor of survival (ratio 1:3.1). The main outcome was survival (unadjusted log-rank test); secondary outcomes were future functional impairments, complications and retrospective carer interviews to determine qualitative benefits and motivations. Enteral feeding is uncommon in UK patients with prion diseases ( n = 26/635; 4.1%), but more frequent in acquired (7/41, 17.1%) and inherited (7/128, 5.5%) compared with sporadic disease (12/466, 2.6%; P = 3 × 10 −5 chi-squared), and used mostly at advanced stages. Enteral feeding was complicated by infection and the need for reinsertions, but associated with markedly longer survival at advanced neurodisability (median 287 days, range 41–3877 versus 17 days, range 0–2356; log-rank test in three aetiologies each P < 0.01). Interviews revealed different motivations for enteral feeding, including perceived quality of life benefits. We provide Class II evidence that enteral feeding prolongs the akinetic-mute phase of all aetiological types of prion disease. These data may help support decision making in palliative care. Enteral feeding is an important potential confounder in prion disease clinical trials that use survival as an endpoint. Abstract : We analysed data from a prospective observational cohort study of UK patients with prion disease. Using a matched case–control design, we found enteral feeding prolongs the akinetic-mute phase of all types of prion disease, but does not appear to preserve useful functions. Enteral feeding was complicated by infections and reinsertions. Graphical Abstract: